2019
DOI: 10.3390/app9051005
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Tomographic Technique and Its Applications

Abstract: X-ray tomography and magnetic resonance imaging (MRI) are excellent techniques for non-destructive or non-invasive inspections, however, they have shotcomings including the expensive cost in both the devices themselves and their protection facilities, the harmful side effects of the X-rays to human bodies and to the environment. In view of this argument, it is necessary to develop new, inexpensive, safe and reliable tomographic techniques, especially in medical imaging and non-destructive inspections. There ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
(18 reference statements)
0
9
0
Order By: Relevance
“…The Young's modulus of the synthesized materials was determined for each sample based on the acoustic velocity measurements. It was found that the Young's modulus increases from 223 MPa to 268 MPa with increasing sintering pressure, which is caused by an increase in the density of the material from 2.09 g/cm 3 to 2.33 g/cm 3 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Young's modulus of the synthesized materials was determined for each sample based on the acoustic velocity measurements. It was found that the Young's modulus increases from 223 MPa to 268 MPa with increasing sintering pressure, which is caused by an increase in the density of the material from 2.09 g/cm 3 to 2.33 g/cm 3 .…”
Section: Discussionmentioning
confidence: 99%
“…During the hydrostatic weighting procedure the kerosene with density 0.784 g/cm 3 (20 °С) was used as a liquid. The density of samples was calculated by the following formula: 𝜌 = 𝑚•0.784 g/sm 3 (𝑚 𝑎 −𝑚 𝑘 )…”
Section: Hydrostatic Weighingmentioning
confidence: 99%
See 1 more Smart Citation
“…Process tomography can give real-time cross-sectional images inside the materials (Martin et al, 2001;Qureshi et al, 2021). A 2-D or 3-D image of some physical quantity inside the object can be obtained using external sensors to detect signals from the boundaries of the object (Dickin and Hoyle, 1992;Schlaberg et al, 1997;Takiguchi, 2019). The measurements variables are usually temperature, pressure, power level, component geometry, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasonic tomography is a non-invasive technique, in which the sensors are mounted outside the pipe to be tested without making any changes to it and it does not interfere with the processes inside the pipe during operation. This technique can give accurate results, and is an environmental-friendly method (Takiguchi, 2019). The ultrasonic signal is transmitted from the transmitter and propagated along the tested material.…”
Section: Introductionmentioning
confidence: 99%